Tin Chemistry 2008
DOI: 10.1002/9780470758090.ch3
|View full text |Cite
|
Sign up to set email alerts
|

Materials Chemistry and Structural Chemistry of Tin Compounds

Abstract: Key indicators: single-crystal X-ray study; T = 130 K; mean (C-C) = 0.003 A ˚ ; R factor = 0.020; wR factor = 0.047; data-to-parameter ratio = 20.7. In the title compound, [Sn(C 2 H 2 O 2 S) 2 (C 2 H 6 OS) 2 ], the mercaptoacetato ligands chelate to Sn IV through S and one O atoms. The metal centre is also coordinated by two dimethyl sulfoxide (DMSO) ligands through the O atom, leading to an overall distorted octahedral coordination environment for the Sn IV atom. The molecular adduct lies on a twofold rotatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…17 It has also been shown that metal complexes with hydrazones can be potent inhibitors of cell growth and DNA syntheses. 18 Tin compounds present applications as PVC stabilizers, 19 for chemical vapor decomposition (CVD), 20 in non-linear optics 21 and in catalyses. 22 Organotin complexes present innumerous pharmacological applications as antitumorals, 23 antimicrobials 24,25 and biocides.…”
Section: Introductionmentioning
confidence: 99%
“…17 It has also been shown that metal complexes with hydrazones can be potent inhibitors of cell growth and DNA syntheses. 18 Tin compounds present applications as PVC stabilizers, 19 for chemical vapor decomposition (CVD), 20 in non-linear optics 21 and in catalyses. 22 Organotin complexes present innumerous pharmacological applications as antitumorals, 23 antimicrobials 24,25 and biocides.…”
Section: Introductionmentioning
confidence: 99%
“…Organotin(IV) complexes have a wide range of applications such as PVC stabilizers [1], for chemical vapor decomposition (CVD) [2], in non-linear optics [3] and in catalyses [4][5][6]. Organotin complexes present innumerous pharmacological applications as antitumorals [7], antimicrobials [8,9] and biocides [10] and locking agent in the formation of dinuclear complexes [11].…”
Section: Introductionmentioning
confidence: 99%